The awareness of internet safety among students in University Utara Malaysia - Rosmawi, Anwar Bazli; Abidin, Rahimi (Universiti Utara Malaysia, 2020)
The growth of the internet gave rise to many important services accessible to anyone with a connection. One of these important services is digital communication. While this service allowed communication with others through the internet, this also allowed communication with malicious users. Common threats to personal safety include phishing, internet scams, malware, cyberstalking, cyberbullying, online predations and sextortion. Thus, this study examine the awareness of internet safety among students, their experience become online victims and their trust in online users.